2021
DOI: 10.1371/journal.pone.0249793
|View full text |Cite
|
Sign up to set email alerts
|

Do mothers who delivered at health facilities return to health facilities for postnatal care follow-up? A multilevel analysis of the 2016 Ethiopian Demographic and Health Survey

Abstract: Introduction Returning to health facility for postnatal care (PNC) use after giving birth at health facility could reflect the health seeking behavior of mothers. However, such studies are rare though they are critically important to develop vigorous strategies to improve PNC service utilization. Therefore, this study aimed to determine the magnitude and factors associated with returning to health facilities for PNC among mothers who delivered in Ethiopian health facilities after they were discharged. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
(53 reference statements)
4
9
0
Order By: Relevance
“…Mothers who had at least one visit by a health eld worker had higher odds of PNC utilisation, a nding similar to that of other studies done in similar contexts [35,36]. The repeated contact with health workers during pregnancy through ANC services and visits by health eld workers promote con dence and familiarity with the health system leading to increased trust in the health system [24]. This emphasizes the need to build capacity among eld health workers, so that they are empowered to counsel women to seek PNC services at the community level in addition to strengthening the services in the health facilities.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Mothers who had at least one visit by a health eld worker had higher odds of PNC utilisation, a nding similar to that of other studies done in similar contexts [35,36]. The repeated contact with health workers during pregnancy through ANC services and visits by health eld workers promote con dence and familiarity with the health system leading to increased trust in the health system [24]. This emphasizes the need to build capacity among eld health workers, so that they are empowered to counsel women to seek PNC services at the community level in addition to strengthening the services in the health facilities.…”
Section: Resultssupporting
confidence: 82%
“…Several studies conducted in Uganda, Ethiopia, Malawi, Zambia and Tanzania, have shown that increased frequency of ANC contacts is associated with higher odds of PNC utilisation [24,27,28,32,33]. Similarly, in this study the odds of PNC utilisation were two times higher among woman who had eight or more ANC contacts compared to their counterparts who had fewer.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Poverty has been associated with poor postpartum nutritional status [37,38], incidence of SSIs [17,39], and poor post-natal care [40]. A study in Ethiopia reported that irrespective of mode of delivery, women with low income were almost half as likely to seek postpartum care [41], and a study in Iran found that rural women who did not received enhanced postpartum follow-up reported poor functional status at six weeks postpartum [41]. Financial hardship faced by poor women in our study could affect post-discharge follow-up and care, and in turn could impede their ability to recover fully.…”
Section: Discussionmentioning
confidence: 99%